Presurgical somatostatin receptor ligand treatment does not affect tumor consistency in GH-secreting pituitary macroadenomas. Issue 1 (January 2021) - Araujo-Castro, Marta; Pian, Héctor; Ruz-Caracuel, Ignacio; Acitores Cancela, Alberto; Pascual-Corrales, Eider; Rodríguez Berrocal, Víctor
Abstract : Purpose: To evaluate whether presurgical treatment using long-acting somatostatin receptor ligands (SRL) may change pituitary tumor consistency and improve surgical outcome in GH-secreting pituitary macroadenomas. Methods: Retrospective study of 40 patients with GH-secreting pituitary macroadenomas operated for the first time by endoscopic transsphenoidal approach. Tumor consistency was evaluated intraoperatively and then correlated with histopathological fibrosis parameters and surgical outcomes. Surgical remission was reported based on the 2010 criteria. Results: The mean tumor size of GH-secreting macroadenomas was of 16.9 ± 8.2 mm and 25 were invasive pituitary adenomas (PAs). Presurgical treatment with long-acting SRL was performed in 17 patients (11 lanreotide, 6 octreotide). The cure rate was higher in those patients pre-treated with monthly doses ≥30 mg of octreotide or ≥90 mg of lanreotide than in those treated with lower doses or untreated (8/11 (72.7%) vs 11/29 (37.9%), P = 0.049). However, although the proportion of soft tumors increased as higher doses of SRL were considered in the pre-treated group, no statistical significance was reached, even when the highest approved monthly doses were used (6/6 (100%) vs 23/34 (67.7%), P = 0.102). Moreover, we found that the remission rate was similar between fibrous and soft tumors ( P = 0.873) and also of surgical complications ( P = 0.859), despite of the higher prevalence of Knosp >2 ( P = 0.035) and very large PA ( P = 0.025) in fibrous tumors than in soft tumors. Conclusions: Although presurgical treatment with high doses of SRL was associated with a 2.2-fold greater chance of surgical remission, this benefit was not related with changes in tumor consistency induced by the presurgical treatment.